A distributed mechanical joint contact model with slip/slap coupling effects. (1st December 2016) - Ahmadian, Hamid; Mohammadali, Mohsen
Abstract: This paper introduces a zero thickness interface model that considers hysteresis effects in both normal and shear directions of a contact. The model is rate independent and represents coupling effects between normal and shear displacements. Contact effects are included through a segment-to-segment contact model which considers stick, micro-slip, slide and slap behaviors at every point within the contact interface. The model has six parameters and three memory variables without the need for integration during response computations. Behavior of the model is validated using the available mechanical joint records in the literature and it is successfully employed for model identification and dynamic response prediction of an internally resonating test structure with frictional support. Highlights: A rate independent contact model representing coupling effects between normal and shear displacements is proposed. The model employs a Hertizian model with hysteresis properties in normal direction and is coupled with the friction model. Assuming a linear relation between transmission from no-slip to sliding and moving from unloading to loading curve, a modified pressure state variable for coupling effect of normal and tangential motion is defined. The contact model parameters are identified using experimentally measured responses.